Understanding learner perspectives on e-learning tools: a case study of the MyIntegrated Reading Companion - Ekalestari, Susi; Kasawi @ Krisnan, Alice Shanthi; Jumaat, Nur Alyaa Fatinah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates students’ perceptions of the MyIntegrated Reading Companion Website as a digital tool for enhancing English language learning. Employing a quantitative descriptive research design, data were collected from 37 students through a 15-item Likert-scale questionnaire. The study aimed to evaluate the website's usability, content organisation, and effectiveness in supporting self-directed learning and motivation. Results show an overall positive response, with an average score percentage of 77.3%. Students particularly appreciated the platform's support for autonomous learning, helpful multimedia features, and the motivation it provided for continued e-learning. The highest-rated items reflected satisfaction with explainer videos and independent learning opportunities. However, slightly lower ratings in areas related to long-term engagement and language improvement suggest a need for more dynamic and adaptive learning content. The findings underscore the potential of the MyIntegrated Reading Companion Website as a useful supplementary tool in English language instruction. Recommendations are made for further content enhancement and continued integration of digital platforms in language education to foster learner motivation and effectiveness.